Clear-sky shortwave downward flux at the Earth's surface: Ground-based data vs. satellite-based data. (February 2019) - Zhang, Taiping; Stackhouse, Paul W.; Cox, Stephen J.; Mikovitz, J. Colleen; Long, Charles N.
Highlights: Reviewed the RadFlux clear-sky shortwave downward fluxes at the BSRN sites. Introduced the GEWEX SRB GSW(V3.0), CERES SYN1deg(Ed4A) and EBAF(Ed4.0) clear-sky data. Compared the satellite-based clear-sky shortwave downward fluxes with RadFlux data. Comparisons show fairly good agreement. Investigated causes for biases and performed bootstrapping analysis of the biases. Abstract: The radiative flux data and other meteorological data in the BSRN archive start in 1992, but the RadFlux data, the clear-sky radiative fluxes at the BSRN sites empirically inferred through regression analyses of actually observed clear-sky fluxes, did not come into existence until the early 2000s, and at first, they were limited to the 7 NOAA SURFRAD and 4 DOE ARM sites, a subset of the BSRN sites. Recently, the RadFlux algorithm was applied more extensively to the BSRN sites for the production of clear-sky ground-based fluxes. At the time of this writing, there are 7119 site-months of clear-sky fluxes at 42 BSRN sites spanning from 1992 to late 2017. These data provide an unprecedented opportunity to validate the satellite-based clear-sky fluxes. In this paper, the GEWEX SRB GSW(V3.0) clear-sky shortwave downward fluxes spanning 24.5 years from July 1983 to December 2007, the CERES SYN1deg(Ed4A) and EBAF(Ed4.0) clear-sky shortwave fluxes spanning March 2000 to mid-2017 are compared with their RadFlux counterparts on the hourly, 3-hourly, daily and monthly time scales. All the three datasets show reasonable agreement with their ground-based counterparts. Comparison of the satellite-based surface shortwave clear-sky radiative fluxes to the BSRN RadFlux analysis shows negative biases (satellite-based minus RadFlux). Further analysis shows that the satellite-based atmosphere contains greater aerosol loading as well as more precipitable water than RadFlux analysis estimates.